An efficient LC-MS method for isomer separation and detection of sugars, phosphorylated sugars, and organic acids. (15th February 2021) - Koley, Somnath; Chu, Kevin L; Gill, Saba S; Allen, Doug K
Abstract : A liquid chromatography–mass spectrometry method that combines hydrophilic interaction chromatography with anion exchange chromatography leads to improved peaks for phosphorylated sugars in plant tissues. Abstract: Assessing central carbon metabolism in plants can be challenging due to the dynamic range in pool sizes, with low levels of important phosphorylated sugars relative to more abundant sugars and organic acids. Here, we report a sensitive liquid chromatography–mass spectrometry method for analysing central metabolites on a hybrid column, where both anion-exchange and hydrophilic interaction chromatography (HILIC) ligands are embedded in the stationary phase. The liquid chromatography method was developed for enhanced selectivity of 27 central metabolites in a single run with sensitivity at femtomole levels observed for most phosphorylated sugars. The method resolved phosphorylated hexose, pentose, and triose isomers that are otherwise challenging. Compared with a standard HILIC approach, these metabolites had improved peak areas using our approach due to ion enhancement or low ion suppression in the biological sample matrix. The approach was applied to investigate metabolism in high lipid-producing tobacco leaves that exhibited increased levels of acetyl-CoA, a precursor for oil biosynthesis. The application of the method to isotopologue detection and quantification was considered through evaluating 13 C-labeled seeds from Camelina sativa . The method provides a means to analyse intermediates more comprehensively in central metabolism of plant tissues.